PENENTUAN HARGA OPSI PUT DAN CALL TIPE EROPA TERHADAP SAHAM MENGGUNAKAN MODEL BLACK-SCHOLES - Marthin Nosry Mooy; Agus Rusgiyono; Rita Rahmawati (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2017)
Option is a contract that gives the right, but not obligation, to individuals to buy (call) or sell (put) certain stocks by a certain price at a specified date. One method that can be used to estimate option price is by using Black-Scholes Model. This model is introduced by Fisher Black and Myron Scholes in 1973. Black-Scholes Model was derived in certain assumptions, such as no dividens, no transaction cost, free-risked interest rates, the option is “European”, and stock price follows a random walk in continuos time, thus the distribution of possible stock prices is lognormal. Application of Black-Scholes Model on Honda Motor Company, Ltd.’s stocks shows that investors can get profits by investing on certain contracts, which is call options with the price of 10,1 US; 8,9 US; and 1,15 US, and also put option with the price of 6,12 US, all with maturity date at January 20th 2017. Keywords: Option, call option, put option, stock, Black-Scholes model.